Cocrystallization of curcumin–isonicotinamide with ultrasonic wave treatment to increase solubility - Wicaksono, Yudi; Seva, Any You; Wisudyaningsih, Budipratiwi; Nuri, Nuri; Susanti, Devi Feby (Faculty of Pharmacy, Universitas Pancasila, 2025)
Curcumin is a polyphenol compound with various biological activities, but its solubility in water is very low (4-8 µg/mL). This research aims to increase the solubility of curcumin through cocrystallization with isonicotinamide coformer. Cocrystallization was carried out using solvent evaporation, which was treated with ultrasonic waves. Cocrystal characterization was carried out using light microscopy, PXRD, DSC, and FTIR. The cocrystal solid was evaluated for solubility using the shaking method, while the dissolution test was carried out in a phosphate buffer medium, pH 6.8, with type II equipment. The results show that cocrystallization with ultrasonic wave treatment produces solid cocrystals (CICoc-Ult) with different solid properties than those without ultrasonic wave treatment (CICoc). CICoc-Ult showed higher solubility and dissolution compared to initial curcumin and CICoc cocrystals. Therefore, ultrasonic wave treatment in the cocrystallization process of curcumin using the solvent evaporation method can be used as a potential strategy to overcome the problem of the solubility properties of curcumin.